2020
DOI: 10.1016/j.agrformet.2019.107813
|View full text |Cite
|
Sign up to set email alerts
|

Impacts of high precipitation on the energy and water budgets of a humid boreal forest

Abstract: The boreal forest will be strongly affected by climate change and in turn, these vast ecosystems may significantly impact global climatology and hydrology due to their exchanges of carbon and water with the atmosphere. It is now crucial to understand the intricate relationships between precipitation and evapotranspiration in these environments, particularly in less-studied locations characterized by a cold and humid climate. This study presents state-of-the-art measurements of energy and water budgets componen… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

2
31
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 28 publications
(33 citation statements)
references
References 88 publications
2
31
0
Order By: Relevance
“…Despite high precipitation, only 45% − 48% returns back to the atmosphere. Isabelle et al [20] in a study at the same sites found that E appeared to be capped even in the presence of high precipitation. The excess of P generates runoff or recharge of ground water, indicating that the availability of soil water is probably not a limiting factor for E T .…”
Section: E T /E At the Seasonal Scalementioning
confidence: 89%
See 2 more Smart Citations
“…Despite high precipitation, only 45% − 48% returns back to the atmosphere. Isabelle et al [20] in a study at the same sites found that E appeared to be capped even in the presence of high precipitation. The excess of P generates runoff or recharge of ground water, indicating that the availability of soil water is probably not a limiting factor for E T .…”
Section: E T /E At the Seasonal Scalementioning
confidence: 89%
“…This study was conducted in a region representative of the humid boreal forest, namely Montmorency Forest in eastern Canada (47 • 17 18 N; 71 • 10 05.4 W) [20]. This region is under the influence of a continental subarctic climate with a short and cool growing season occurring between June and October [51].…”
Section: Study Sitementioning
confidence: 99%
See 1 more Smart Citation
“…They are equipped with eddy covariance sensors (IRGASON, Campbell Scientific, UT, USA) that measure turbulent fluxes of heat and water vapour (snow sublimation and evapotranspiration), and CNR4 net radiometers (Kipp and Zonen, Delft, the Netherlands). Further details about the flux towers is provided by Isabelle et al [55]. An intensive manual snow survey was conducted during winters 2016-2017 (W1) and 2017-2018 (W2) around each snow-profiling station, for a total of 1061 observations.…”
Section: Methodsmentioning
confidence: 99%
“…Due to past logging operations, there are several patches of forest clearings accompanied by spatially varying stand structures ( Figure 1). For detailed descriptions of the study area, please refer to Parajuli et al [51], Isabelle et al [52,55] and Hadiwijaya et al [54]. turbulent and radiative fluxes between the canopy and the atmosphere.…”
Section: Study Areamentioning
confidence: 99%